2007
DOI: 10.1073/pnas.0700625104
|View full text |Cite
|
Sign up to set email alerts
|

Platelet glycoprotein Ibα supports experimental lung metastasis

Abstract: The platelet paradigm in hemostasis and thrombosis involves an initiation step that depends on platelet membrane receptors binding to ligands on a damaged or inflamed vascular surface. Once bound to the surface, platelets provide a unique microenvironment supporting the accumulation of more platelets and the elaboration of a fibrin-rich network produced by coagulation factors. The platelet-specific receptor glycoprotein (GP) Ib-IX, is critical in this process and initiates the formation of a platelet-rich thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
125
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(131 citation statements)
references
References 54 publications
4
125
1
1
Order By: Relevance
“…Adherent platelets present potent adhesion receptors such as JAM-C, P-Selectin, GPIb␣, or GPIIb/IIIa to other circulating cells providing a platform for a potent cellular bridging mechanism to the vascular wall (20,25,(52)(53)(54)(55)(56). Recently, glycoprotein Ib␣ (GPIb␣), the second most abundant receptor expressed on platelets, has been reported to be significantly involved in melanoma metastasis, as the functional absence of GPIb␣ correlated with a clear reduction in the number of lung metastatic foci in vivo (57). In contrast, another report showed that GPIb␣ inhibition led to a significant increase in pulmonary metastasis, improved survival, and pulmonary arrest of tumor cells (58), presumably reflecting the complexity of tumor cellplatelet-endothelial interactions and manifesting the need for continued experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…Adherent platelets present potent adhesion receptors such as JAM-C, P-Selectin, GPIb␣, or GPIIb/IIIa to other circulating cells providing a platform for a potent cellular bridging mechanism to the vascular wall (20,25,(52)(53)(54)(55)(56). Recently, glycoprotein Ib␣ (GPIb␣), the second most abundant receptor expressed on platelets, has been reported to be significantly involved in melanoma metastasis, as the functional absence of GPIb␣ correlated with a clear reduction in the number of lung metastatic foci in vivo (57). In contrast, another report showed that GPIb␣ inhibition led to a significant increase in pulmonary metastasis, improved survival, and pulmonary arrest of tumor cells (58), presumably reflecting the complexity of tumor cellplatelet-endothelial interactions and manifesting the need for continued experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…The identified molecules may not only serve as disease markers, but are evidently eminent contributors to disease progression. To give examples, GP1BA and 12S-HETE are known as powerful tumor promoters (47,61). Most importantly, the altered platelet functions may be considered as surrogate markers for manifest systemic reprogramming of distant organ sites in metastatic melanoma, mainly resulting from calcium mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cell lodging and subsequent adhesion to endothelial cells may be one of the most rate-limiting steps of the metastatic cascade (41,42). Different mechanisms have previously been implicated in the adhesion of tumor cells to endothelial cells including the involvement of E-selectin and P-selectin, the binding to coagulation factors like fibrin or tissue factor as well as a contribution of platelets (43)(44)(45)(46). Likewise, several lung endothelial cell-expressed molecules have been implicated in lung-specific metastasis.…”
Section: Discussionmentioning
confidence: 99%